A Review of Hardware-In-The-Loop Simulation for Control Performance Verification of Permanent Magnet Synchronous Motors - Li, Wenjuan; Tian, Dezheng (Recent Patents on Engineering, 2025)
BackgroundIn previous developments of permanent magnet synchronous motor tests, physical experiments provided results closest to actual working conditions. However, these experiments had long development cycles, increased costs, poor repeatability, and potential risks of damage to equipment and casualties if not handled carefully. The introduction of hardware-in-the-loop real-time simulation technology has effectively addressed these challenges in motor testing development. Therefore, the development of hardware-in-the-loop simulation technology holds significant importance.ObjectiveThe existing real-time simulation platforms summarize specific examples of the current use of real-time simulation, and classify the hardware-in-the-loop simulation of permanent magnet synchronous motors to predict its development trend.MethodsThe study analyzes the characteristics of existing real-time simulation platforms and their suitability for different environments. It also examines the modeling methods and real-time simulation techniques for permanent magnet synchronous motors under various circumstances, assessing their feasibility and accuracy, control strategies for permanent magnet synchronous motors are compared and expounds and compares the latest patented technologies.ResultsThe hardware-in-the-loop simulation system of the permanent magnet synchronous motor is analyzed and compared, and its typical features are summarized. Additionally, the problems in the hardware-in-the-loop simulation system are analyzed, and the future development trend is discussed.ConclusionCompared to the simulation results of actual motors, the results obtained from hardware-in-the-loop simulation are highly accurate. The utilization of hardware-in-the-loop simulation platforms can effectively decrease development costs, shorten the research and development cycle, and minimize the risks associated with experiments in specific cases when testing permanent magnet synchronous motor systems. Additionally, it enhances the reproducibility of experiments.
Keywords: Permanent magnet synchronous motor